Novel RB1 and MET Gene Mutations in a Case with Bilateral Retinoblastoma Followed by Multiple Metastatic Osteosarcoma - Mokánszki, Attila; Chang Chien, Yi-Che; Mótyán, János András; Juhász, Péter; Bádon, Emese Sarolta; Madar, László; Szegedi, István; Kiss, Csongor; Méhes, Gábor (Diagnostics (Basel), 2020)
Retinoblastoma (Rb) is a malignant tumor of the developing retina that affects children before the age of five years in association with inherited or early germline mutations of the RB1 gene. The genetic predisposition is also a driver for other primary malignancies, which have become the leading cause of death in retinoblastoma survivors. Other malignancies can occur as a consequence of radiotherapy. We describe a patient with retinoblastoma in which we detected a novel RB1 c.2548C > T, p.(Gln850Ter) and a synchronous MET c.3029C > T, p.(Thr1010Ile) mutation as well. After presenting with bilateral retinoblastoma, the patient developed at least four different manifestations of two independent osteosarcomas. Our goal was to identify all germline and somatic genetic alterations in available tissue samples from different time periods and to reconstruct their clonal relations using next generation sequencing (NGS). We also used structural and functional prediction of the mutant RB and MET proteins to find interactions between the defected proteins with potential causative role in the development of this unique form of retinoblastoma. Both histopathology and NGS findings supported the independent nature of a chondroblastic osteosarcoma of the irradiated facial bone followed by an osteoblastic sarcoma of the leg (tibia).